Peran Hukum Islam dan Kearifan Lokal dalam Membangun Toleransi dan Kerukunan di Masyarakat Plural - Sari, Zeti Nofita; Warjiyati, Sri (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
This study explores the role of Islamic law and local wisdom in fostering tolerance and harmony within a plural society. The research aims to understand how the integration of Islamic values and local cultural practices can contribute to peaceful coexistence among diverse religious groups. Using a normative research method, the study focuses on analyzing the framework of Islamic law and cultural practices that promote religious tolerance in Indonesia. The findings show that local wisdom, when combined with Islamic legal principles, plays a significant role in maintaining social unity. The discussion emphasizes the importance of contextualizing Islamic teachings to align with local customs. This study concludes that the synergy between Islamic law and local wisdom is essential in shaping a legal framework that supports tolerance and harmony in plural societies.